Algoritmo de machine Learning en el reconocimiento de imágenes. - Quinto Rodríguez, Denecis Noemy (2024)
Image recognition using Machine Learning (ML) is a subarea of artificial intelligence (AI) that seeks to enable computers to interpret and understand images in a manner similar to humans. This research focuses on the use of convolutional neural networks (CNNs), which are specifically designed to process gridded data, such as images. The study addresses the processes involved in image recognition, including data collection and preparation, model selection, training, and evaluation. The use of ML in this area is justified due to its high accuracy, automation capability, and adaptability to new tasks, resulting in a significant reduction of human effort. The research is framed in the line of information and communication systems, with a focus on improving efficiency and accuracy in visual pattern identification, also addressing challenges related to biases in training data.